# Mistake in expression

While attempting to multiply the expression (2 - 5i)(5 + 2i), a student made a mistake.

(2 - 5i)(5 + 2i) = 10 + 4i - 25i - 10i2

= 10 + 4(-1) - 25(-1) - 10(1)

= 10 - 4 + 25 - 10

= 21

Complete the explanation and correct the error.

Hint: The student incorrectly defined i as being equal to ___ instead of ___. The student should have written the product as :

(2 - 5i)(5 + 2i) = 10 + 4i - 25i - 10i2

= 10 + 4(-1) - 25(-1) - 10(1)

= 10 - 4 + 25 - 10

= 21

Complete the explanation and correct the error.

Hint: The student incorrectly defined i as being equal to ___ instead of ___. The student should have written the product as :

## Correct answer:

Tips for related online calculators

Try our complex numbers calculator.

### You need to know the following knowledge to solve this word math problem:

## Related math problems and questions:

- Scientific notation mul

A student found the product of 8 × 10³ and 7 × 10^{5}to be 5.6 × 10^{8}. What is the error? What is the correct product? Complete the explanation. - Pool

If water flows into the pool by two inlets, fill the whole for 20 hours. The first inlet filled the pool 8 hour longer than the second. How long does the pool take to fill with two inlets separately? - Evaluate with brackets

Find the Error - tell what the mistake is 6[(4 + 9) - 32] ÷ 2 6[13-32]÷2 6[13-9]÷2 6[9]÷2 6[4.5] 27 - Jiwan

Jiwan Incorrectly Wrote 1+ 1/2 + 1/3 + 1/4 =1 3/9 Show The Correct Working And Write Down The Answer As A Mixed Number.

- Danny

Danny made a mistake in the following problem. Line 1:21 + 35 ÷ 7 + 6(2) Line 2:21 + 5 + 6(2) Line 3:21 + 11(2) Line 4:21 + 22 Line 5:43 On what line was the mistake made? Only input the number of the first incorrect line. - Mistake

Nicol needs to correct errors when calculating in school. Instead of adding the number 20, she subtracts it. What is the difference between the result and the correct result? - Describe 11

Describe and correct the error in finding the difference function of (f-g) (x) of f(x) =(x²+3x-1) and g(x) =(x²+x+2) (f-g) (x) =f(x)-g(x) =(x²+3x-1) - (x²+x+2) =x²+3x-1 -x²+x+2 =x²-x²+3x+x-1+2 =4x+1